If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-5) + 7p = -5 Multiply -2 * -5 10 + 7p = -5 Solving 10 + 7p = -5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 7p = -5 + -10 Combine like terms: 10 + -10 = 0 0 + 7p = -5 + -10 7p = -5 + -10 Combine like terms: -5 + -10 = -15 7p = -15 Divide each side by '7'. p = -2.142857143 Simplifying p = -2.142857143
| 6-2r=-2+2r | | -69=3(-3x-2) | | 20f+(-8f-15)=12f-15 | | (-4y^2+5d)-(2y^2)= | | 1.2=5.18 | | 10n+18=2+8n | | 0.6x-8=12 | | 2y-2z=3 | | -60x=17x+77 | | 2(400-x)+3=1050 | | 24=3-2y | | 0.6x-8=-12 | | 4(8-4r)=48 | | 0.5x=x+20 | | -18+9x=7x-4 | | 24=3y-2 | | 14d-2e+3e-13d= | | 2s-1000=4400 | | (-12a^9-13u)-(-13a^9)= | | 4.5q-5.8-5.5q=2.0q-3.3 | | 6y+2=5x | | 8-6k=k-6 | | 2(3x-4)=4(2x+3) | | .5y=.5x+.5 | | 100=4t^2-24t+36 | | 100-6y=-60 | | -78=-6(p-4) | | 8x+4x+3+6=4x+3+7x | | 3(p-3)-5p=-36-6 | | (6x+6)-(5x+10)= | | x-4=9+2 | | n+2=10n+10n-6 |